Strengthening salt reduction policy for Malaysia through proposed maximum salt targets of selected processed food groups - Ong, Ying Qian; Shahar, Suzana; Haron, Hasnah; Malek Rivan, Nurul Fatin; Mohamad, Hamdan; Abdul Manan, Musaalbakri; Wan Ibadullah, Wan Zunairah; Michael, Viola; Pombo-Rodrigues, Sonia; He, Feng J; MacGregor, Graham A (Nature Research, 2025)
The World Health Organization recommends a daily salt intake of less than 5.0 g. Similarly, Malaysia’s Salt Reduction Strategy to Prevent and Control Non-communicable Diseases (2021–2025) targets a daily intake of less than 6.0 g by 2025, achievable through salt reduction in processed and prepared foods. However, the lack of maximum salt targets for food businesses to adhere to, poses a potential challenge to the effectiveness of salt reduction efforts. This paper presents a step-wise approach to propose maximum salt targets in key food categories, paving the way for mandatory or voluntary policy interventions. Following a step-wise approach by Downs et al. (2015) for setting national salt targets, this study systematically proposed maximum salt targets for selected food categories. Steps included: (1) identifying major contributors to dietary salt (2) selecting target food categories; and (3) establishing target levels. Steps 1 and 2 were performed by reviewing literature from local dietary survey and analyzing street food nutrient content as well as retrieving secondary data from previous market surveys. An additional market survey was conducted in February 2024 following the gazettement of mandatory sodium labelling in January 2024. Scatter plot analysis, literature reviews and expert consultations were used to achieve Step 3. Step 1 identified that the major contributors to Malaysia’s salt intake are cooked food and processed foods. A total of 14 food categories under the Food Regulation 1985 were selected for target setting based on their contribution to dietary salt intake and relevance to ongoing revision in the Malaysia Food Act 1983 (Step 2). The 75th percentile sodium level was selected as the maximum salt target and adjusted by a further 10–20% reduction based on sales data from a reputable source (Step 3). This study proposed maximum salt targets for 14 food categories, which are recognised as major contributors to salt intake in Malaysian diets. There is a need to further engage with stakeholders and develop monitoring mechanisms to support the implementation of maximum salt targets as well as evaluating consumer behaviour changes.